Design optimizations of carbon fibre reinforced polymer isogrid lower limb prosthesis using particle swarm optimization and Lichtenberg algorithm. Issue 11 (2nd November 2021) - Francisco, Matheus Brendon; Junqueira, Diego Morais; Oliver, Guilherme Antônio; Pereira, João Luiz Junho; da Cunha Jr, Sebastião Simões; Gomes, Guilherme Ferreira
Abstract : The demands for a high-performance prosthesis include high strength and low weight. This study addresses the optimization of a new tube concept, made of composite material, which makes use of an isogrid and internal layer. For the methodological procedure, a response surface methodology (RSM) was used to define in what quantity, under what conditions and which data should be collected during a given experiment, seeking to satisfy the highest statistical precision and the lowest cost in the response. After RSM analysis, the finite element method was used for structural calculations for each condition of the experiment. The numerical results allowed the creation of a meta-model capable of translating the global structural behaviour. Thus, it was possible to optimize the parameters that were translated as responses applied to a lattice structure by particle swarm optimization and the Lichtenberg algorithm (LA). Comparison of the results demonstrated the good performance of the LA.